Diferenciais no comportamento reprodutivo das mulheres Brasileiras: uma análise a partir dos grupos ocupacionais - Cláudio Santiago Dias Júnior (Universidade do Estado do Rio de Janeiro, 2010)
The aim of this study was to analyze reproductive behavior based on women's occupation in the work market. The hypothesis is that given occupations are associated with different strategies by women in relation to fertility, resulting in different reproductive histories. The study used the database from the Population Census for 2000 conducted by the Brazilian Institute of Geography and Statistics (IBGE). Women's birth histories were reconstructed, and demographic tools were used to perform a descriptive analysis of the relationship between women's reproductive behavior and their occupation. According to the findings, women in more highly qualified occupational groups tended to have fewer children and postpone motherhood longer.